Extended RAS analysis for anti-epidermal growth factor therapy in patients with metastatic colorectal cancer. Issue 8 (September 2015) - Hecht, J. Randolph; Douillard, Jean-Yves; Schwartzberg, Lee; Grothey, Axel; Kopetz, Scott; Rong, Alan; Oliner, Kelly S.; Sidhu, Roger
<x xml:space="preserve">Abstract</x> Highlights Panitumumab and cetuximab are effective therapies for metastatic colorectal cancer. KRAS exon 2 mutation status has been used to guide anti-EGFR therapy. Many patients have tumors with other RAS mutations (KRAS exon 3/4; NRAS exons 2/3/4). Recent evidence indicates that these mutations can also guide anti-EGFR therapy.